Development of an emergency department end of life care audit tool: A scoping review - Melissa Heufel; Sarah Kourouche; Kate Curtis (Elsevier, 2023)
Introduction: Emergency departments frequently care for patients at the end of life and should have robust processes for reviewing delivery of care. The aim of this scoping review is to examine and collate the chart audit tools available to assess the quality of end of life care of patients who die in the emergency department, or, in the subsequent hospital admission. Methods: A scoping review of the literature using the PRISMA-ScR (Preferred Reporting Items for Systematic reviews and Meta-Analyses extension for Scoping Reviews) guidelines, and the methodological framework outlined by Arksey and O'Malley was conducted. Primary and secondary research, along with grey literature were searched. Both adult and paediatric populations were included. Databases Ovid Emcare, CINAHL and Medline were searched from 1961 to December 2022; followed by screening and appraisal. Articles were compared and data synthesised into categories. Results: Fifty-eight articles were included generating three categories; contexts for end of life audit use, development and evaluation of audit tools, and audit characteristics / components. Four tools focused on the emergency department, however, did not comprehensively review both end of life and emergency department specific data. A draft audit tool for the emergency department was developed that consisted of the common elements to evaluate end of life care as identified in this review, emergency department-specific quality of care measures and the integration of the Criteria for Screening and Triaging to Appropriate aLternative care (CriSTAL) tool. Conclusion: No audit tool to comprehensively review end of life care provided for patients at the end of life in the emergency department was found. We developed an audit tool based on best available evidence that now needs testing for validity, feasibility, and usability to evaluate end of life in the emergency department setting is required.